An exploratory study on the role of family functioning in the dietary adherence of type 2 DM patients in Metro Manila - Gillana, Cena Marie B.; Mallari, Mariel Keziah S.; Suguitan, Isaiah Emmanuel D.
Type 2 diabetes mellitus (T2DM) is a prevailing health problem among many Filipinos characterized by chronic elevation of blood glucose. Management strategies on T2DM mostly revolve around lifestyle and nonpharmacologic strategies which involve proper diet and exercise. Family support has also been reported to be vital in T2DM management with its role in promoting one’s adherence to T2DM dietary recommendations. However, family functioning defined as “the process of nurturing…that promotes emotional and physical growth and maturation of all members” (Smilkstein, 1978, p. 1232) remains to be an unexplored gap in reported studies relative to dietary adherence. This study explored the role of family functioning to the dietary adherence of Filipino T2DM patients by looking at their lived experiences. Five (5) patients diagnosed with T2DM from the last 1-3 years along with two (2) of their family members were invited for an in-depth semi-structured interview. The study identified four (4) themes on family functioning namely: family utilization of resources to cope with illness, family’s flexibility to adjust to changes, family connectedness in the face of illness, and family communication. The study also found that family functioning plays a role in dietary adherence and vice versa. Thus, considering a patient’s family functioning can help better facilitate dietary adherence to Type 2 DM dietary recommendations.